South African midwives’ knowledge of the benefits of delayed umbilical cord clamping - Akhona Shosha; Wanda Jacobs; Zelda Janse van Rensburg (South African Family Practice)
Background: Immediate umbilical cord clamping has been part of the active management of the third stage of labour for centuries. Despite the benefits of delayed cord clamping, immediate cord clamping remains the routine practice in many countries, including South Africa. The aim of this study was to determine South African midwives’ knowledge of the benefits of delayed umbilical cord clamping.